ANALISIS KIMIA BATANG AREN (ARENGA PINNATA MERR) DARI JASINGA, BOGOR - Gusmailina Gusmailina; Hartoyo Hartoyo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Chemical analyses of Aren stem (Arenga pinnata Merr) from Jasinga, Bogor has been conducted at the Forest Products Research and Development Centre laboratory in Bogor. The analyses comprised of the determination of cellulose, lignin, pentosan, ash and silica, calorific value, extractioes and the solubility in sodium hydroxide. These analyses were commonly conducted to determine basic characteristics and ultimate uses of wood.The average of the cellulose, lignin, pentosan, ash and silica, extractives content, solubility in sodium hydroxide and calorific value of the peripheral portion were consecutively as follow: 25,02%, 33,7%, 19,55%, 1,4 and 0,51%,6,65 % (in cold water), 10,06 % (in hot water), 3,86 % (in alcohol-benzene), 35,51 % in sodium hydroxide and 4406 kal/g. While for the central portion, the above analyses showed averages as follow : 44,82 %, 36,8 %, 16,57 %, 4,18 % and 1,32 %, 22,88 % (in cold water), 32, 74 % (in hot water), 4,82 % (in alcohol-benzene), 59,80 % in sodium hydroxide and 4035 kal/g. The extractive content of Aren stem ranked high in the characteristics and ultimate uses of wood classification.Based on chemical analyses, such as the cellulose content, lignin, peniosan and extractive content, the Aren stem from Jasinga, Bogor, appeared to be a poor materipl for pulp and paper industry.